RELIGIUSITAS SEKAA TERUNA GIRI MUSTIKA WERDHI DALAM MENUNJANG AKTIVITAS KEAGAMAAN DI KAWASAN WISATA DESA ADAT KUTUH KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Ni Kadek Febri Antari; I Ketut Mardika; I Nyoman Kiriana (UHN IGB Sugriwa Denpasar, 2020)
Religion is a stick for guiding people who are blind to the moral values and religious norms that go on in society. Sekaa Teruna is one of the traditional organizations in Bali today. This organization serves as a forum for developing adolescent creativity. In addition, this organization is also expected to be a place to preserve local culture and traditions. However, in the modern era that tends to lead to the development of science and technology, society, especially the younger generation, develops to negative things. The meaning of religion in the view of the younger generation today is still considered as a supplement that is needed at any time. There are five forms religiosity of sekaa teruna that is ngayah in the framework of piodalan, ngayah mereresik, prayers purnama and tilem, tirta yatra, otonan ceremony, and cultural arts activites.